IMPLEMENTASI MEDIA PEMBELAJARAN DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK DI SEKOLAH DASAR NEGERI RAWAILAT CILEUNGSI KABUPATEN BOGOR - Fitrah Hamzih (PT. Hasba Edukasi Mandiri, 2025)
This research is based on the belief that learning media can inspire students to learn more efficiently. The purpose of this thesis is to answer the problem formulation question about the role of learning media in increasing students' learning motivation at Rawailat Cileungsi State Elementary School, Bogor Regency. This research is a qualitative descriptive study using a spiritual, psychological, and pedagogical approach. The types of data used in this study are primary and secondary data. Primary data sources consist of the principal, homeroom teacher, Islamic religious education teacher, physical education and health teacher, and students. The conclusion of this study shows that the implementation of learning media at Rawailat Cileungsi State Elementary School, Bogor Regency, is running well. The effective efforts made by educators in using learning media to increase student motivation are: first, teachers prepare themselves by mastering the material so that teachers will be ready and easy to carry out lessons in class. Second, teachers prepare learning media according to student needs and learning materials and understand how to use them. Third, teachers direct students to the attention function or direct students to concentrate so that it is easier for students to receive the lesson. Fourth, by using interesting learning media, it will encourage students to be active in discussions and active in questions and answers. By using interesting learning media, there will be more student involvement in learning. Fifth, teachers direct students to the evaluation function to determine whether or not learning in using learning media is successful.